YALIcloneNHEJ: An Efficient Modular Cloning Toolkit for NHEJ Integration of Multigene Pathway and Terpenoid Production in Yarrowia lipolytica - Li, Ya-Wen; Yang, Cai-Ling; Shen, Qi; Peng, Qian-Qian; Guo, Qi; Nie, Zhi-Kui; Sun, Xiao-Man; Shi, Tian-Qiong; Ji, Xiao-Jun; Huang, He (Frontiers in Bioengineering and Biotechnology, 2022)
Non-homologous end-joining (NHEJ)-mediated random integration in Y. lipolytica has been demonstrated to be an effective strategy for screening hyperproducer strains. However, there was no multigene assembly method applied for NHEJ integration, which made it challenging to construct and integrate metabolic pathways. In this study, a golden-gate modular cloning system (YALIcloneNHEJ) was established to develop a robust DNA assembly platform in Y. lipolytica. By optimizing key factors including amounts of ligase and reaction cycles, the assembly efficiency of 4, 7 and 10 fragments reached up to 90, 75 and 50%, respectively. This YALIcloneNHEJ system was subsequently applied for the overproduction of the sesquiterpene (-)-α-bisabolol by constructing a biosynthesis route and enhancing the flux in the mevalonate pathway. The resulting strain produced 4.4 g/L (-)-α-bisabolol, the highest titer reported in yeast to date. Our study expands the toolbox of metabolic engineering and is expected to enable highly efficient production of various terpenoids.